2002
DOI: 10.1117/12.467388
|View full text |Cite
|
Sign up to set email alerts
|

MARS2: An Advanced Femtosecond Laser Mask Repair Tool

Abstract: Femtosecond pulsed lasers offer fundamental advantages over other techniques for repairing lithographic masks. Since the femtosecond ablation process is non-thermal, the spatial resolution is not degraded by thermal diffusion and is therefore limited only by optical diffraction. In addition, metal splatter, gallium staining, reduced optical transmission, beam induced charging, quartz damage, and phase errors inherent in other repair methods are eliminated.A second generation femtosecond laser repair tool is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The second generation of the mask repair system (MARS II) has been installed in late 2001 as IBM's primary repair tool for 248 nm and 193 nm wavelength chrome on glass phase shift photolithographic masks [93]. In this system, a frequency-tripled Ti:sapphire femtosecond laser beam (260 nm, 100 fs, 1 kHz) is focused to a diffraction limited 150 nm Gaussian spot and scanned over the defect to remove it.…”
Section: Repair Of Photolithography Masksmentioning
confidence: 99%
See 1 more Smart Citation
“…The second generation of the mask repair system (MARS II) has been installed in late 2001 as IBM's primary repair tool for 248 nm and 193 nm wavelength chrome on glass phase shift photolithographic masks [93]. In this system, a frequency-tripled Ti:sapphire femtosecond laser beam (260 nm, 100 fs, 1 kHz) is focused to a diffraction limited 150 nm Gaussian spot and scanned over the defect to remove it.…”
Section: Repair Of Photolithography Masksmentioning
confidence: 99%
“…An ablation resolution of 80 nm together with an increased flexibility in ablating complex structures were demonstrated. Mask features were trimmed to a root-meansquare precision of ~ 5 nm [93].…”
Section: Repair Of Photolithography Masksmentioning
confidence: 99%
“…Extended defects were removed by scanning the photomask stage under the focused beam. It was reported that the imaged aperture approach did not produce high-quality sub-wavelength laser zaps due to diffraction effects, thus the focused beam was chosen for semiconductor mask repairs where sub-wavelength nanometer-scale opaque defect ablation has priority 14 .…”
Section: Laser Module and Optical Configurationmentioning
confidence: 99%
“…By carefully matching Gaussian distribution of the laser beam intensity profile to the ablation threshold of either Chrome or Mo-Si film on the glass substrate, sub-wavelength spatial resolution of ablation was achieved with an ultrafast DUV laser (266 nm, 100 fs) and 0.9NA DUV objective lens 8,14 . Extended defects were removed by scanning the photomask stage under the focused beam.…”
Section: Laser Module and Optical Configurationmentioning
confidence: 99%